Compact Lithium-Niobate-on-Insulator Polarization Rotator Based on Asymmetric Hybrid Plasmonics Waveguide - Yiru Zhao; Wenqi Yu; Shuangxing Dai; Jinye Li; Tao Lin; Mingxuan Li; Jianguo Liu (IEEE Photonics Journal, 2021)
We proposed a compact and efficient polarization rotator (PR) based on an asymmetric hybrid plasmonics waveguide (HPW) on the lithium-niobate-on-insulator (LNOI) platform. We focus on the design of rotation angle and balance between the two hybrid modes. The presented device exhibits a polarization extinction ratio as high as 59.58 dB and an insertion loss of 1.44 dB with the rotation length of only 13.7 $μ$ m. The fabrication tolerances and a suitable process are also discussed to meet the state-of-art technology.